Perspektif Ulama Sumedang Terhadap Perjalanan Ibadah Haji, Gelar dan Akhlak Spritual Muslim dalam Pendidikan Agama Islam - Radan Arifin Putra; Dendi Agustiana; Muhamad Rizki; Muhamad Samsul Hidayatulloh; Ray Antariksa; Tedi Supriyadi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study investigates the interaction between the Hajj pilgrimage, the title "Haji/Hajjah," and spiritual morals in the religious journey of Muslims in Sumedang Regency. This research seeks to answer three main research questions: (1) How is the title of Hajj socially constructed within Sumedang society? (2) How does the Hajj pilgrimage influence an individual's behavior and beliefs? and (3) What role does Islamic religious education play in aligning religious titles with daily morality? The study is based on the fact that the term "Hajj" is often used as a symbol of social status, despite the essence of Hajj being the transformation and internalization of Islamic values. The phenomenological method was employed through in-depth interviews with scholars, pilgrims, and community members, supplemented by participatory observation and documentation research. Data were analyzed through phenomenological reduction, imaginative variation, and synthesis of meaning. The study shows that although performing the Hajj can improve the quality of worship, sincerity, and social concern, the title of Hajj is often "commodified" as a social status without accompanying significant moral change. Instead, an individual's behavior is more highly valued by society today than a formal title. Based on the study's results, the religious education curriculum should be strengthened by emphasizing sincerity, simplicity, and the internalization of noble morals so that religious titles truly reflect a genuine spiritual journey.